Symbiotic performance of Medicago ciliaris lines in association with different Sinorhizobium strains - Aouani, M. Badri, S. Soula, T. Huguet, M.E. (Journal of Ecobiotechnology, 2009)
We analyzed nodulation and nitrogen fixation efficiency for seven lines of Medicago ciliaris in association with two references strains of Sinorhizobium medicae (M104) and S. meliloti (RCR2011). These M. ciliaris lines were collected in Northern-East (Enfidha and Soliman) and Western (Rhayet and Mateur) Tunisian areas. The M. truncatula reference line Jemalong A17 (JA17) was also included. Plants were harvested after a culture period of 60 days. Two quantitative traits were measured at the harvest including the mean number of nodules per plant and the aerial dry weight (ADW). Analysis of variance showed that nodulation and nitrogen fixation efficiency (NFE) were dependent on the effects of line, strain and their interaction. The highest levels were observed for strain (45.07%) and line (53.24%) effects, respectively, for nodulation and NFE. While studied lines showed generally more number of nodules with RCR2011, they were more efficient with M104 strain. No significant difference in number of nodules was detected between M. ciliaris lines and JA17 with M104, whereas RCR2011 was generally most infective with JA17. Overall, JA17 line exhibited the largest NFE with both strains. Furthermore, there was no significant (P>0.05) correlation between nodulation and NFE for M. ciliaris line by strain associations.